Duration of symptoms before diagnosis in degenerative cervical myelopathy: A systematic review and meta-analysis - Ailish Malone; Maram Sofiany; Ghalia Dawood; James Wright; Rody Ryan; Caroline Treanor; Conor Gallagher; Warren Lenehan; Frank Doyle; Ciaran Bolger (Brain and Spine)
Introduction: Degenerative cervical myelopathy (DCM), the commonest cause of spinal cord injury, can lead to progressive disability. Due to overlapping symptoms with other conditions and low awareness among healthcare professionals, many patients experience delayed diagnosis. Research question: What is the typical duration of symptoms of DCM before diagnosis? Materials and methods: We searched multiple databases for primary studies reporting duration of symptoms in people with confirmed diagnosis of DCM. Two independent reviewers screened titles, abstracts, full-text articles, extracted data and appraised study quality. We performed random-effects meta-analyses to pool duration of symptoms to presentation, diagnosis, and intervention. Results: We identified 78 studies from 18 countries, with 12,450 participants. Time from symptom onset to first clinical presentation (two studies, n = 232 participants) was 3.3 (95 % confidence interval, −0.3-6.8) months. Time from symptom onset to diagnosis (five studies, n = 897) was 15.0 (5.0–25.0) months. In 29 studies (n = 3052) that measured from symptom onset to surgery/pre-operative assessment the duration was 14.5 (12.1–17.0) months. Thirty-seven studies had an undefined endpoint, in which when pooled, duration of symptoms was 15.2 (12.4–18.0) months. Most studies did not define the symptoms at onset, however when onset was defined as first occurrence of myelopathic (upper motor neurone) symptoms (five studies, n = 1006), time to surgery was 10.7 (2.3–18.5) months. Discussion and conclusion: Most people with DCM experience symptoms for more than one year before diagnosis. These data may be useful to inform initiatives to promote early diagnosis. Standardised methodology would improve further research in this area.